2001
DOI: 10.1007/bf02234640
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography of the pelvic floor musculature in the assessment of obstructed defectation symptoms

Abstract: Either activation or inhibition appears as a physiological behavior, possibly adopted in different circumstances, of the pelvic floor muscles during attempted defecation. The higher prevalence of coordinated inhibitory patterns in normal subjects and the lower frequency of pubococcygeus muscle inhibition in patients with symptoms of obstructed defecation, however, suggests that a loss of inhibition capacity progressing from pubococcygeus muscle to puborectalis muscle/external sphincter muscles could determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
0
20
1
1
Order By: Relevance
“…In the literature, there is discussion on the action of the pubococcygeal muscle as to whether this muscle plays a role in giving rectal support against an increased abdominal pressure [Fucini et al, 2001] Signs suggestive of pelvic £oor muscle dysfunction. Signs are observed by the examiner, including simple means, in order to verify symptoms and quantify them.…”
Section: Terminologymentioning
confidence: 98%
“…In the literature, there is discussion on the action of the pubococcygeal muscle as to whether this muscle plays a role in giving rectal support against an increased abdominal pressure [Fucini et al, 2001] Signs suggestive of pelvic £oor muscle dysfunction. Signs are observed by the examiner, including simple means, in order to verify symptoms and quantify them.…”
Section: Terminologymentioning
confidence: 98%
“…It has been claimed that the Pcm in humans belongs to the levator ani complex (Jundt et al, 2005) and participates in fecal and urinary continence (Fucini et al, 2001). In male rats, this muscle is not part of the levator ani complex (Yuan et al, 2003); however, its participation in micturition and ejaculation is highlighted through behavioral studies (Manzo et al, 2000) and by electrical stimulation of its nerve (Manzo et al, 1997).…”
mentioning
confidence: 99%
“…Anorectal manometry can be used to study the relationship between rectal pressure and volume as well as assess rectal capacity and compliance by measuring anorectal resting pressure, anorectal squeeze pressure, rectal reflex contraction, external anal sphincter relaxation reflex, and inducing the initial rectal sensory pressure and urgent defecation pressure. Some scholars have suggested that outlet obstruction constipation is related to abnormal rectal sensation and weakened rectal wall contractility [9]. This finding suggests that anorectal sensory nerve damage may be a main reason for major clinical symptoms in patients.…”
Section: Discussionmentioning
confidence: 75%
“…If the pelvic floor contracts rather than relaxes during bowel movement, the action leads to constipation. Previous studies have found that in patients with posterior rectal wall prolapse and outlet obstruction, the external sphincter, puborectalis, and pubococcygeal muscles were more excited during defecation than in the resting state [9]. After electric stimulation therapy for rectal sensation was administered by Chang [6] and others to patients with functional constipation and impaired rectal sensation, rectal sensation increased and symptoms improved.…”
Section: Discussionmentioning
confidence: 99%